Diary of a wimpy kid:the last straw - Kinney, Jeff (Amulet Books, New York., 2009)
Middle-schooler Greg Heffley nimbly sidesteps his father's attempts to change Greg's wimpy ways until his father threatens to send him to military school
Keywords: diary of a wimpy kid, english fiction